Methodology For Developing The Physical Education Of Primary School Children - Abdullayev Dilshod Khamidullo (Genius Journals, 2024)
This article examines the methodology for developing the physical activity of primary school children by analyzing existing scientific literature, creating a new methodology, and successfully enhancing the physical movement capabilities of primary school-aged children.
Keywords: physical development; physical preparation; physical qualities